دراسة تحليلية صرفية في لفظ الغفران ومشتقاته في القرآن - Amin Nasir (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2020)
AbstractIf the Arabic language is written and spoken, you will find the application of morphological rules in the words of forgiveness and their derivatives in the Qur’an. In terms of form in the adverbial grammar it is divided into two parts: the first in terms of time of occurrence of the function, and the second in terms of derivation or sentence changes that have similar meanings taken from other similar examples. In terms of verb: past tense, present tense, verb imperative, in terms of the derivation it includes: infinitive, participle noun, object noun, time and place noun, and so on. After conducting a search on the 'words of forgiveness' and its 'derivatives' in the Qur’an, it was found that there are 211 words, 54 letters and 198 verses. As for the types and meanings of 'words of forgiveness' and 'derivatives thereof' in the Qur’an, they differ according to the form of the sentence in it. From this research there are six forms: Past tense, Present tense, Imperative verb, Infinitive, and participle noun. In the past tense there are 4 expressions, in the present tense 13 pronunciations, the verb imperative 8 pronunciations, the participle noun there are 3 pronunciations, the source there are 3 expressions and the form of exaggeration 4 words. Whereas the meanings contained in the word forgiveness and its derivatives in the Qur’an there are five types: first in terms of the abstract triple meaning the meaning of the jacket and tolerance, the second in terms of the act of forgiveness with 3 additional letters that has the meaning of forgiveness or the triple, and the third has the meaning of exaggeration, which is a substance that is forgiven a lot, and the fourth It is the name of God Almighty or the names of the Most Beautiful, and the fifth has the meaning of the command or the command. Among the various forms of 'the words forgiveness' and 'longing for forgiveness' in the Qur’an have meanings that have the meanings of forgiveness, which are 'forgiveness', 'forgiveness', 'forgiveness' and 'disbelief'. Type to know the type of shape and meaning of words. So the sentence context also determines knowing the meaning in the sentence